Ergonomic in the callcenter context: Protocol of the Ergonomic Work Analysis of the Telemarketing - Bormio, M. [UNESP]; Guanetti dos Santos, J. E. [UNESP]; Placido da Silva, J. C. [UNESP]; Pereira das Neves, E. [UNESP]; Arezes, P. M.; Baptista, J. S.; Barroso, M. P.; Carneiro, P.; Cordeiro, P.; Costa, N.; Melo, R. B.; Miguel, A. S.; et al. (Crc Press-taylor & Francis Group, 2016)
Work has been constantly aim of study in its differents forms. To comprehend how could be this developing and to establish a good interface between it and the human being has been a great challenge. Among the wide range of approaches that can be made by ergonomics, mention it specifically the importance of the Ergonomic Work Analysis, whose main aims are the constant searching for identifying and supplying possibles troubles of this interface and configuring a workplace conditions (environments, furniture and tools) and processes that are guiding by safety and psychophysics health of the worker. In this context, emphasize it the importance of adequate methodologic tools for auxiliary in this process. This paper introduces the PAETT (Protocol of the Ergonomic Work Analysis of the Telemarketing), that was developed starting from diagnose of the lack of methodological tools for realizing Ergonomic Post Occupancy Analysis in Callcenter environment. The PAETT has a multidisciplinary approach that can be applied of the way objective and technic by evaluator and subjective by worker's point of view who develops the activity. To understand it that with the results made applying the PAETT is possible to render interventions more punctual and consequently obtain optimized aims.